Analisis Promosi Kesehatan Berbasis Keluarga Dengan Self-Care Pada Ibu Hamil Dengan Diabetes Melitus Gestasional Di RS Mitra Sejati - Martaulina Sinaga; Adriana Bangun; Adelina Fitri Tanjung; Catrine Indriany Simaremare; Lamro Hasibuan; Juliana Amnum Harahap (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Background: Gestational Diabetes Mellitus (GDM) is a pregnancy-related condition that can increase the risk of maternal and neonatal complications. The management of GDM requires adequate self-care practices, including dietary regulation, physical activity, glucose monitoring, adherence to antenatal care, and stress management. Family-based health promotion is needed to strengthen mothers’ ability to perform self-care continuously. Objective: To analyze the relationship between family-based health promotion and self-care among pregnant women with GDM at Mitra Sejati Hospital. Methods: This study employed a quantitative analytical approach with a cross-sectional design. A total of 75 pregnant women with GDM were selected using consecutive sampling. Data were analyzed using univariate and bivariate analyses with the Chi-Square test at a significance level of α = 0.05. Results: Most respondents received family-based health promotion in the moderate category (42.7%) and demonstrated good self-care (57.3%). Among respondents who received good family-based health promotion, 80.0% demonstrated good self-care, whereas only 27.8% of those who received inadequate health promotion demonstrated good self-care. The Chi-Square test showed a statistically significant relationship between family-based health promotion and self-care (p = 0.003). Conclusion: Family-based health promotion is significantly associated with self-care among pregnant women with GDM.